IbM MESIN PENGOLAH SAMPAH RUMAH TANGGA UNTUK MENUNJANG PROGRAM PEMBANGUNAN DI BIDANG KEBERSIHAN DI KOTA BENGKULU - Ahmad Fauzan Suryono; Afdhal Kurniawan Mainil; Gusta Gunawan (Universitas Bengkulu, 2018)
The aim of this community service is to improve the environment and public health in the city of Bengkulu, and the success of the human development index in the health sector. While the goal in particular is the amount of waste in the landfill can be significantly reduced over time so that the cleanliness of the environment and health can be realized, can boost the economic value of the plastic waste from households because it can be sold to a factory producing plastic pellets and machinery This can help people who are interested in waste processing technology to become entrepreneurs plastic pellets. This activity lasted for ten months in cooperation with two partners, namely the Parks Department and Sanitation of Bengkulu and CV Terang Bulan engaged in the sale of plastic waste. In implementing this program assisted with the research team of students to design and create a municipal waste processing machine a plastic which is more practical with affordable production costs for society. On completion of this machine in addition to the stages involves students will also involve CV. Terang Bulan as a partner in business who have started this garbage. The partners are expected to play an active role in providing fill-enter on the specifications desired by the user. After making machines is completed then it is disseminated to the public that waste management is important and profitable economically. Keywords: Waste Processing Machines, Seeds plastic, household waste